Constraints Faced by Deoni Cattle Rearers and Non-descriptive Cattle Rearers in the Adoption of Management Practices - B. L. Pisure , Deshmukh P. R and Thombre B. M, (Indian Journal of Extension Education, 2016)
The present study was conducted purposively in Latur district of the Marathwada region of Maharashtra state. 120respondents of Deoni cattle and 120 respondents of Non-descriptive cattle from Latur district were selected. Thus, therewere a total of 240 respondents selected for the research study. Ex-post facto research design was adopted in this study.The data were collected with the help of pretested interview schedule. It was found that, deoni cattle rearers were lack ofknowledge about management of pregnant cow and newly born calf was the most important constraint (91.67 %) in themanagement of pregnant cow and newly born calf followed by lack of knowledge about improved dairy productionpractices (90.00 %) and lack of contact between dairy farmers and veterinarians (76.00 %) was reported as secondaryconstraints reported by deoni cattle rearers. Inadequate knowledge about breeding practices (94.17 %). While nondescriptive cattle rearers seeking knowledge about improved dairy production practices (93.33 %) was reported as majorproblem followed by lack of knowledge about management of pregnant cow and newly born calf (92.50 %) and lack ofcontact between dairy farmers and veterinarians (76.67 %). However, it was reported that inadequate knowledge aboutbreeding practices (97.50 %) was the major constraint in adoption of breeding management practices.